Exploring resilience and transformation post The Great Disruption: A comparative analysis of firm performance in the new normal era (A COVID-19 literature study) - Kusnan Kusnan; Rahmi Aryanti; Ria Astriyani; Junaidi Junaidi (Priviet Social Sciences Journal, 2026)
The Covid-19 Pandemic has brought significant changes in humankind’s social life worldwide. Furthermore, both on a micro and macro scale, fundamental changes in economic life are companies in developed and developing countries. This study aims to determine the impact this pandemic has had on many companies in these two country categories and find essential lessons that can be used to overcome similar pandemics in the future. We conclude that the business world, in particular, will change significantly after this Pandemic and many essential things must be prepared to face the company activities in the new normal or post-pandemic era